Examining the Postsecondary Enrolment of Low-Income Mature Students in Canada - Victoria A Fritz; Tricia van Rhijn (Canadian Society for Studies in Education, 2019)
This exploratory study deepens current understandings of low-income mature students in Canadian postsecondary institutions, by clarifying who constitutes this population and through providing demographic characteristics that describe this population of study. Individual, family, and institutional characteristics of low-income mature students were examined using 2011 Survey of Labour and Income Dynamics data. Low-income mature students were predominantly male, studying full-time in university, and averaged 33.29 years of age.  In addition, comparisons of gender and institutional differences indicated that female low-income mature students were older and had more children and larger household sizes. Low-income mature students in college were more likely to have children and had larger household sizes. Overall, 5% of all post-secondary students were found to be low-income mature students, suggesting that this is not an insignificant population. This study is the  first to examine the enrolment patterns of Canadian low-income mature students and demonstrates that further study of this unique group is required.